The Institutional Adjustment Margin to Import Competition: Evidence from Italian Minimum Wages - Alessia Matano; Paolo Naticchioni; Francesco Vona (Institute of Labor Economics (IZA), 2019)
A growing body of research has contributed to understanding the labor market and political effects of globalization. This paper explores an overlooked aspect of trade-induced adjustments in the labor market: the institutional aspect. We take advantage of the two-tier collective bargaining structure of the Italian labor market, whereby the first tier entails setting minimum wages at the contract level. Using an instrumental variable strategy and exploiting variations in contract-level exposure to trade, we find for the 1995-2003 period that, on average, the surge in imports decreased contractual minimum wages by 1.5%. This impact increases in the share of unskilled workers employed in the contract. This negative institutional effect contrasts with a nonsignificant effect of trade on total wages, with the latter becoming positive and large only for highly skilled workers.
Keywords: J50; F16; J31; J24; 330; bargained minimum wages; import competition; labor market institutions; skills